Study of Several Aspects of Fishery for Guiding Barrier Fishing Gear in The Coastal Town Palopo - Sukimin, Ridwan; Danial, Danial; Rauf, Abdul (Jurnal Biologi Tropis, 2021)
Fishing is a profession that has long been carried out by humans and is estimated to have been thousands of years old. Sero is one of the many types of fishing gear that is often operated by coastal fishermen, especially in the Palopo City area. Fish, crabs, squids, lobsters, turtles and even estuarine crocodiles are just a few examples of variations in the types of marine life that can be trapped in sero fishing gear. Along with the growth of human population and advances in fishing technology, the level of exploitation is increasing. On the other hand, the carrying capacity of the environment, including fish resources, has limitations. The increasing number of fishing activities accompanied by the reduction of catch targets also causes competition between fishermen to compete for these resources often occurs. These things then motivated the author to conduct a scientific study in the hope that the results of this study can be one of the basis for the preparation of regulations, especially with regard to the use of sero-type fishing gear in Palopo City. The purpose of this research is to examine the existence of sero fishing gear in relation to potential conflicts, business contribution, types of catch, selectivity, and estimated catch to fishing effort. The research method used includes qualitative and quantitative analysis of several respondents who were selected either randomly (purpuse sampling) or based on a commonly used formula. The data obtained from the respondents are based on the results of interviews, both through filling out closed and open questionnaires. In addition to data from interviews, other necessary data are taken from government agencies, the results of previous research by experts, or taken directly at the research location. Based on the results of the study, the potential conflict between the use of sero fishing gear against other fishing gear users only has the potential to use traps, throwing nets, and hand lines. comparison of financing (R/C), and categorized quickly through analysis of return on investment (PP). The types of sero fishing gear caught consisted of 33 species of fish, 7 species of crustaceans, and 1 species of mollusk. The variety of species caught also proves the level of selectivity of fishing gear sero fishermen in Palopo City is categorized as medium based on species diversity analysis (H’) and low category based on dominance analysis (D). The results in this study also prove that the level of selectivity of fishing gear sero fishermen in Palopo City is very low even though the level of exploitation of fisheries resources in Palopo City is actually still in the developing stage. Things that can be recommended based on the results of this study are the efficiency of the number of sero fishing gear and the use of mesh sizes as well as increasing efforts to conserve mangroves as a source of primary productivity.